Taguchi modeling and optimization of laser processing in machining of substantial industrial PVC foam - Subramonian, Sivarao; Robert, Milkey; Samsudin, Abdul Rahim (2013)
This paper presents of how Taguchi modeling leads into the optimization of laser processing in solving industrial problems to cut thick foam establishing high dimensional accuracy. The thick PVC foam is widely used by industries to establish sandwich panels for marine applications. The experimental studies were critically screened to conduct under influential design parameters, namely, cutting speed, laser power, frequency, duty cycle, and gas pressure. The final design setting was determined by Taguchi method, where, ANOVA was employed to investigate the significance level of design parameters. The optimized set of laser parameters was determined by the analysis of signal-tonoise (S/N) ratio. The model validation through experimental work indicated how Taguchi can actually be used to model and optimize the response (kerf width & taper) within the acceptable range of the manufacturing industries. This investigation reveals on how a non-linear laser processing can actually be modeled and optimized using Taguchi for the benefit of precision manufacturing industries.